Genetics of Alzheimer's Disease - Ibanez, Laura; Miller, Justin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This special issue on the genetics of Alzheimer's disease was edited by Drs. Laura Ibanez and Justin Miller in 2021. It contains 10 original articles and reviews that help readers understand specific genetic contributions to Alzheimer's disease and how genetics will play a role in future Alzheimer's disease research.